This Odd and Wondrous Calling: The Public and Private Lives of Two Ministers - Plekon, Michael (Cistercian studies quarterly, 2011)
The article reviews the book "This Odd and Wondrous Calling: The Public and Private Lives of Two Ministers," by Lillian Daniel and Martin B. Copenhaver.